2000
DOI: 10.1103/physrevc.61.034611
|View full text |Cite
|
Sign up to set email alerts
|

Microcanonical studies concerning the recent experimental evaluations of the nuclear caloric curve

Abstract: The microcanonical multifragmentation model from [Al. H. Raduta and Ad. )] is refined and improved by taking into account the experimental discrete levels for fragments with A ≤ 6 and by including the stage of sequential decay of the primary excited fragments. The caloric curve is reevaluated and the heat capacity at constant volume curve is represented as a function of excitation energy and temperature. The sequence of equilibrated sources formed in the reactions studied by the ALADIN group ( 197 Au+ 197 Au a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…Here a 1 = 0.001 MeV −1 , and a 2 ≈ 0.009-0.015 MeV −2 slightly depends on the projectile energy. It should be noted that the adopted correlation of the mass number with the excitation energy is consistent with dynamical simulations [29,30], as well as with results of other statistical models [6,7,12]. Besides providing a very good description of fragment production at different Z bound , the calculations with this kind of ensemble also correctly reproduce the behavior of the caloric curve [18].…”
Section: Theoretical Calculations With Ensembles Of Equilibrated supporting
confidence: 71%
See 1 more Smart Citation
“…Here a 1 = 0.001 MeV −1 , and a 2 ≈ 0.009-0.015 MeV −2 slightly depends on the projectile energy. It should be noted that the adopted correlation of the mass number with the excitation energy is consistent with dynamical simulations [29,30], as well as with results of other statistical models [6,7,12]. Besides providing a very good description of fragment production at different Z bound , the calculations with this kind of ensemble also correctly reproduce the behavior of the caloric curve [18].…”
Section: Theoretical Calculations With Ensembles Of Equilibrated supporting
confidence: 71%
“…There are large fluctuations of the fragment multiplicity and of the size of the largest fragment in the transition region from a compound-like decay to full multifragmentation of spectators [3]. It was found that the statistical models, which assume a thermal equilibration among hot fragments in a freeze-out volume at subnuclear densities, are fully consistent with the data [4][5][6][7].…”
Section: Introductionmentioning
confidence: 93%
“…5 represent the results for 600 MeV per nucleon [51], with small modifications due to additional experimental information and corrections, and the results for 1000 MeV per nucleon obtained more recently [52]. The temperature of the transition region is close to that obtained with the dynamical [49] or statistical models [7,53,54] and does not change with the bombarding energy. In contrast to it, the energy associated with the spectator source increases by, on the average, 30% over the range 600 to 1000 MeV per nucleon, a behavior inconsistent with the universality of the spectator decay that so clearly appears in other variables [21].…”
Section: Liquid-gas Phase Transitionmentioning
confidence: 95%
“…It is motivated by the differences of the wave lengths and time scales governing the entrance and exit channels and justified by the remarkable success of statistical approaches for the second stage [5][6][7]. The intermediate states are not necessarily equivalent to hot nuclei but should be, more generally, viewed as systems of highly excited nuclear matter, populating a phase space characterized by global quantities like mass, charge, energy, density or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Finally generated events are filtered to account for the experimental device. Detailed presentations of models can be found in references [17,105,110,111,112]. Within such an approach the input parameters: mass and charge of the system at break-up density, its excitation energy, its volume at freeze-out and the eventual added radial expansion have to be backtraced to experimental data, estimated from dynamical simulations or derived from data related to properties of systems at break-up.…”
Section: Statistical Descriptions Of Multifragmentationmentioning
confidence: 99%